2009
DOI: 10.1158/0008-5472.can-08-4419
|View full text |Cite
|
Sign up to set email alerts
|

Mutation-Independent Anaplastic Lymphoma Kinase Overexpression in Poor Prognosis Neuroblastoma Patients

Abstract: Anaplastic lymphoma kinase (ALK) is a receptor tyrosine kinase predominantly expressed in the developing nervous system. Recently, mutated ALK has been identified as a major oncogene associated with familial and sporadic neuroblastomas (NBL). Yet, a direct correlation between endogenous expression level of the ALK protein, oncogenic potential, and clinical outcome has not been established. We investigated ALK genetic mutations, protein expression/ phosphorylation, and functional inhibition both in NBLderived c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
138
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(162 citation statements)
references
References 38 publications
(61 reference statements)
19
138
2
3
Order By: Relevance
“…Consequently, in neuroblastomas, highest ALK expression levels (and not moderate levels) were significantly correlated with the most aggressive tumors. 27 Genetic aberrations were only found in a small number of patients in our cohort, suggesting that the majority of ES patients harbor wild-type ALK, although we cannot exclude aberrations outside the investigated domains. Interestingly, three patients harbored sporadic ALK translocations, although the fusion partners and significance of these translocations in a small subset of tumor cells is yet unknown.…”
Section: Discussionmentioning
confidence: 80%
“…Consequently, in neuroblastomas, highest ALK expression levels (and not moderate levels) were significantly correlated with the most aggressive tumors. 27 Genetic aberrations were only found in a small number of patients in our cohort, suggesting that the majority of ES patients harbor wild-type ALK, although we cannot exclude aberrations outside the investigated domains. Interestingly, three patients harbored sporadic ALK translocations, although the fusion partners and significance of these translocations in a small subset of tumor cells is yet unknown.…”
Section: Discussionmentioning
confidence: 80%
“…Fusion proteins arising from somatic rearrangements have been reported in anaplastic large cell lymphomas and other tumours (reviewed in [Palmer et al, 2009]). In NB and NB cell lines, both ALK amplification and gain-of-function missense mutations of conserved codons of the TKD have been reported [Chen et al, 2008;George et al, 2008;Janoueix-Lerosey et al, 2008;Passoni et al, 2009]. Some experimental data indicate variable oncogenic potential of ALK mutants with p.F1174L having an increased transforming capacity compared to p.R1275Q and p.K1062M [Chen et al, 2008;De Brouwer et al, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…Activating mutations in ALK are found in a large majority of familial cases of neuroblastoma, which account for approximately 2% of all cases of neuroblastoma, and ALK gene mutations or gene amplifications have been identified in up to 15% of sporadic high-risk neuroblastoma cases [19,118]. Furthermore, wild-type ALK expression is elevated in high-risk compared to low-risk neuroblastoma tumors [119]. A subsequent phase I trial using the ALK inhibitor crizotinib in children with relapsed and refractory neuroblastoma has been completed [120], and further studies have identified synergistic combinations of ALK and mTOR inhibitors [121], suggesting a potential role for ALK inhibitors in the treatment of children with tumors with mutant ALK.…”
Section: Treatment -Relapsed and Refractory Neuroblastomamentioning
confidence: 99%